OPTIMAL CONTROL OF INVESTMENTS IN A DYNAMIC MODELS OF DUOPOLY - Y. Aganin (Publishing House of the State University of Management, 2017)
The paper studies profit maximization in three dynamic models of duopoly. The first one describes the dynamics of production and capital-labor ratio with equilibrium price, the second - the same problem with non-equilibrium price and the third one analyzes the optimal external financing of capital expenditures and working capital.